Biocarvões pirolíticos: efeitos em atributos físicos do solo e na cultura do milho - Moniz, Tiago da Costa Dantas (2024)
The application of carbonaceous materials is strategic for improving soil quality and agricultural productivity. However, depending on the biomass used, different outcomes are observed in the soil's chemical, physical, and biological properties. Therefore, it is not yet known how doses of biochars produced from sewage sludge and cashew residues influence the soil's physical attributes. (1) biochars derived from the pyrolysis of sewage sludge added with cashew pruning biomass (BLP) and cashew processing residues (BC) improve the physical quality of degraded soil and the development of maize; (2) BLP, being richer in nutrients, enables better maize development compared to BC; (3) for each biochar, there is a most effective dose to improve the physical quality of soil undergoing degradation and the development of maize. Soil samples (Planosol) were collected from the 0-10 cm layer in the desertification nucleus of Irauçuba-CE. The experiment was set up in a completely randomized design, in a 2 x 4 + 1 factorial scheme, totaling 36 experimental units. Plant development was monitored by measuring height, stem diameter, number of leaves, leaf area, and fresh and dry matter production. At the end of the experiment, and before soil removal, samples with preserved and unpreserved structures were collected from the center of the 0-10 cm layer to evaluate soil density, soil penetration resistance, soil air permeability, water retention curve, tensile strength, and aggregate stability. As a result, BC reduced water requirement by 40% at the dose of 9 Mg ha-1. BLP reduced soil density by 4% at the dose of 22.6 Mg ha-1 but also reduced soil air permeability. BLP improved soil penetration resistance and aggregate stability, increasing tensile strength and mean weight diameter. Both biochars increased soil water retention capacity and reduced moisture at the permanent wilting point. Regarding plant growth, there was an increase in stem diameter with both biochars, being more pronounced with BLP at the dose of 23.2 Mg ha-1. BLP also contributed to an increase in stem diameter and a reduction in plant height, enhancing resistance to lodging. It is concluded that BLP improves the physical quality of the soil to a greater extent than BC, which, in turn, optimizes water use efficiency. The recommended doses are 20-25 Mg ha-1 for BLP and 9 Mg ha-1 for BC